2014
DOI: 10.1017/s0033291714000397
|View full text |Cite
|
Sign up to set email alerts
|

Impaired integration of disambiguating evidence in delusional schizophrenia patients

Abstract: Background. It has been previously demonstrated that a cognitive bias against disconfirmatory evidence (BADE) is associated with delusions. However, small samples of delusional patients, reliance on difference scores and choice of comparison groups may have hampered the reliability of these results. In the present study we aimed to improve on this methodology with a recent version of the BADE task, and compare larger groups of schizophrenia patients with/without delusions to obsessive-compulsive disorder (OCD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 39 publications
5
66
0
2
Order By: Relevance
“…Another literature indicates that patients are overconfident in their false judgements pertaining to memory, perception and social cognition [4,5]. Finally, a number of studies indicate that patients with psychosis are less open to counter-arguments, even for delusion-neutral scenarios [6].…”
Section: Cognitive Biases In Psychosismentioning
confidence: 99%
“…Another literature indicates that patients are overconfident in their false judgements pertaining to memory, perception and social cognition [4,5]. Finally, a number of studies indicate that patients with psychosis are less open to counter-arguments, even for delusion-neutral scenarios [6].…”
Section: Cognitive Biases In Psychosismentioning
confidence: 99%
“…[3][4][5][6][7][8] One prominent construct refers to disturbed evidence gathering; patients with delusions display a jumping-to-conclusions thinking style (i.e., they make inferences based on limited evidence). 4,9 A second construct pertains to a certain incorrigibility, which manifests as disturbed integration of disambiguating or disconfirmatory evidence 7,[10][11][12] and increased confidence in false judgments. 13,14 Evidence gathering and incorrigibility have been shown to be largely independent from each other, 15,16 though intercorrel ated to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…In a prior theoretical paper it was outlined that the integration of disconଏrmatory evidence might be a risk factor for the maintenance of delusions (Garety et al, 2001). Supporting this theory, multiple experimental studies also revealed that a BADE was speciଏcally associated with delusion severity (Riccaboni et al, 2012;Sanford et al, 2014;Speechley et al, 2012;So et al, 2012;Woodward et al, 2006b). Some other studies which did not observe associations between BADE and delusions discussed BADE as a potential trait-factor for delusions rather than a state-dependent bias (Moritz and Woodward, 2006;Veckenstedt et al, 2011).…”
Section: Introductionmentioning
confidence: 94%